2003
DOI: 10.1086/346088
|View full text |Cite
|
Sign up to set email alerts
|

The Chandra Deep Field North Survey. XIV. X-Ray–Detected Obscured AGN[CLC]s[/CLC] and Starburst Galaxies in the Bright Submillimeter Source Population

Abstract: We provide X-ray constraints and perform the first X-ray spectral analyses for bright SCUBA sources ( f 850µm ≥ 5 mJy; S/N≥ 4) in an 8. ′ 4 × 8. ′ 4 area of the 2 Ms Chandra Deep Field-North survey containing the Hubble Deep Field-North. X-ray emission is detected from seven of the ten bright submm sources in this region down to 0.5-8.0 keV fluxes of ≈ 1 × 10 −16 erg cm −2 s −1 , corresponding to an X-ray detected submm source density of 360 +190 −130 deg −2 ; our analyses suggest that this equates to an X-ray… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
28
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 165 publications
(32 citation statements)
references
References 113 publications
(162 reference statements)
4
28
0
Order By: Relevance
“…The rest-frame 1.4 GHz luminosities were calculated for S82 by assuming a uniform spectral slope of α = −0.7, following Alexander et al (2003) 3 . For the C3GHz sample, the 1.4 GHz fluxes were taken from the VLA-COSMOS 1.4 GHz survey (Schinnerer et al 2007) when available, and calculated from the 3 GHz fluxes assuming a uniform spectral slope of α = −0.7 otherwise.…”
Section: Final Radio-detected Samples: S82 and C3ghzmentioning
confidence: 99%
“…The rest-frame 1.4 GHz luminosities were calculated for S82 by assuming a uniform spectral slope of α = −0.7, following Alexander et al (2003) 3 . For the C3GHz sample, the 1.4 GHz fluxes were taken from the VLA-COSMOS 1.4 GHz survey (Schinnerer et al 2007) when available, and calculated from the 3 GHz fluxes assuming a uniform spectral slope of α = −0.7 otherwise.…”
Section: Final Radio-detected Samples: S82 and C3ghzmentioning
confidence: 99%
“…SMGs harbouring hidden AGNs is not a new concept, and in some sources, Xray observations have already revealed obscured AGNs (e.g. Alexander et al 2003;Borys et al 2005). Although both Chandra and XMM-Newton have observed the field, the observations targeted the foreground X-ray bright galaxy cluster making it difficult to resolve and disentangle emission from the QSO and companion.…”
Section: Quasar-star-forming Companion Systemsmentioning
confidence: 99%
“…Ultra-deep Chandra observations (the 2 Ms Chandra DeepField-North survey; Alexander et al 2003a) have shown that at least ≈28-50% of the bright SMG population host heavily obscured AGNs (e.g., Alexander et al 2003bAlexander et al , 2005aAlexander et al , 2005c, implying joint growth of the galaxy and black hole (see also Ivison et al 2002;Wang et al 2004;Pope et al 2006). 9 The energetics of the AGNs measured at X-ray and mid-infrared (mid-IR) wavelengths are (typically) too low to explain the huge bolometric output of these objects (L bol ≈ 10 12 -10 13 L ; e.g., Ivison et al 2004;Alexander et al 2003bAlexander et al , 2005aLutz et al 2005), which appears to be dominated by star-formation processes (as shown by the strong star-formation signatures in the mid-IR spectra; e.g., Menéndez-Delmestre et al 2007;Valiante et al 2007;Pope et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…9 The energetics of the AGNs measured at X-ray and mid-infrared (mid-IR) wavelengths are (typically) too low to explain the huge bolometric output of these objects (L bol ≈ 10 12 -10 13 L ; e.g., Ivison et al 2004;Alexander et al 2003bAlexander et al , 2005aLutz et al 2005), which appears to be dominated by star-formation processes (as shown by the strong star-formation signatures in the mid-IR spectra; e.g., Menéndez-Delmestre et al 2007;Valiante et al 2007;Pope et al 2008). 10 However, the large AGN fraction implies that the black holes are growing almost continuously throughout periods of vigorous star formation.…”
Section: Introductionmentioning
confidence: 99%